PREDICTION OF TB NOTIFICATIONS AT GWERU PROVINCIAL HOSPITAL USING ARTIFICIAL NEURAL NETWORKS - DR. SMARTSON. P. NYONI ,; THABANI NYONI, (International Journal of Innovations in Engineering Research and Technology, 2021)
In this research article, the ANN approach was applied to analyze TB notifications at Gweru District Hospital (GDH). The employed data covers the period January 2010 to December 2019 and the out-ofsample period ranges over the period January 2020 to December 2021. The residuals and forecast evaluation criteria (Error, MSE and MAE) of the applied model indicate that the model is stable in forecasting TB notifications at GPH. The results of the study indicate that TB case notifications are likely to increase over the period January 2020 to December 2021. In order to contribute meaningfully to the national control strategy of a TB-free Zimbabwe, GPH should, among other things, intensify TB surveillance and control programmes in its catchment area.